2018
DOI: 10.3750/aiep/02299
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of juvenile fish species in nursery grounds of a tropical coastal area of the south-western Atlantic

Abstract: Background. Assessing patterns in habitat utilization and changes in the composition of biont assemblages is a key tool for efficient ecosystem conservation planning and management. Nevertheless, habitat use patterns by juvenile fish still need more comprehension. Therefore, the presently reported study investigated relations between the type of nursery ground and the structure of juvenile fish assemblages in a tropical coastal area of the south-western Atlantic. Materials and methods. From December 2009 to No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…Recent studies have pointed to the presence of six taxonomically recognized Mugil species in the Coral Coast MPA: Mugil brevirostris , M. curema , M. curvidens , M. incilis , M. liza , M. rubrioculus (da Silva, Teixeira, Batista, & Fabré, 2017, 2018; Torres et al., 2008), although the distribution of M. incilis has been contested (Menezes et al., 2015). Our study used 11 morphological traits to test whether the individuals identified as belonging to these six species are morphologically different.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have pointed to the presence of six taxonomically recognized Mugil species in the Coral Coast MPA: Mugil brevirostris , M. curema , M. curvidens , M. incilis , M. liza , M. rubrioculus (da Silva, Teixeira, Batista, & Fabré, 2017, 2018; Torres et al., 2008), although the distribution of M. incilis has been contested (Menezes et al., 2015). Our study used 11 morphological traits to test whether the individuals identified as belonging to these six species are morphologically different.…”
Section: Discussionmentioning
confidence: 99%
“…Their stomach contents were assessed under a stereomicroscope until 70 non-empty stomachs per species and estuary could be gathered. As densities for the two jack species are rather low in estuaries during the wetter months of the year (Vilar et al, 2011;Silva-Júnior et al, 2017;da Silva et al, 2018), fish from different years had to be pooled to reach a minimum number of 10 non-empty stomachs for both the dry (September to March) and the rainy (April to August) seasons in the area (CPRH, 2003;2003a), and a maximum of 30 individuals per year for each estuary. Prey items in all stomachs were identified to the lowest taxonomic level possible, depending on their degree of digestion.…”
Section: Fish Sampling and Diet Compositionmentioning
confidence: 99%
“…In estuaries, physico-chemical gradients (e.g. in salinity) drive food web structure and determine habitat suitability for fish (Barletta et al, 2008;da Silva et al, 2018). However, food abundance also modulates interactions between potential competitors (Sánchez-Hernández et al, 2017;Costa-Pereira et al, 2019).…”
Section: Possibility For Trophic Competitionmentioning
confidence: 99%
“…Com base no período de amostragem, não foi possível determinar épocas de desova. No entanto, estudos anteriores revelaram que peixes do gênero Lutjanus, L. jocu e L. alexandrei são endêmicas e dependentes de áreas costeiras, como manguezais e recifes, principalmente durante seu período reprodutivo (Osório;Godinho & Lotufo, 2011;Pinheiro & Farias, 2016;Aschenbrenner;Hackradt & Ferreira, 2016), assim como os membros da família Gerreidae coletados nesse estudo, D. Auratus e E. Argenteus (Viana et al, 2016;Pereira & Pessanha, 2017;Silva et al, 2018). A ausência de organismos adultos na área amostrada possivelmente indica que os indivíduos coletados não completam seu ciclo de vida no mangue (Pinheiro & Goitein, 2014), utilizando-o apenas como berçário e zona de alimentação.…”
Section: Espécieunclassified